A simple model of PV system performance and its use in fault detection - Steven Firth; Kevin Lomas; Simon J. Rees (2010)
Results are presented from a monitoring study of the performance of a sample of UK domestic PV systems. Five minutely average climatic and performance data was recorded for 27 PV systems at two sites for up to two years of operation. On average, the annual energy losses due to faults were 3.6% (Site A, first year of operation), 6.6% (Site A, second year of operation) and 18.9% (Site B, first year of operation). Simple empirical models are constructed to describe the performance of the PV systems under ‘normal operation’ (when no faults occur). New analysis techniques are developed which estimate the energy losses of four different fault categories: sustained zero efficiency faults; brief zero efficiency faults; shading; and non-zero efficiency non-shading faults. The results demonstrate that faults have the potential to cause significant energy losses in domestic PV systems. The benefits of applying the data analysis techniques described in this work to PV system clusters and other urban micro-generation technologies are discussed.